Electromagnetic Mind Control : Fact or Fiction? A Scientific View. - Binhi, V. N. (New York : Nova Science Publishers, Incorporated, 2010)
Although there are many publications in newspapers and popular magazines, discussing "Electromagnetic Mind Control" and "Electromagnetic Weapons," it is almost impossible to find reliable information on these issues, particularly where relatively weak electromagnetic (EM) radiations are of concern. This book fills the gap. Written for a general audience, it discusses the physics of and related scientific information on brain control using EM fields. It provides a balanced scientific viewpoint on the possibility of the effects of EM on the human brain and mind. The book considers --current methods of EM information extracting from and delivery into the human brain --general theoretical principles of EM field interactions with living objects --modern experiments, including neurological ones --the microwave hearing effect and technical limitations of the targeted exposure of humans to EM fields --methodological limitations regarding EM mind control.
Intro -- ELECTROMAGNETIC MIND CONTROL: FACT OR FICTION? A SCIENTIFIC VIEW -- ELECTROMAGNETIC MIND CONTROL: FACT OR FICTION? A SCIENTIFIC VIEW -- Library of Congress Cataloging-in-Publication Data -- Contents -- Foreword -- References -- Acknowledgments -- Chapter 1: Introduction -- Mind Control -- Mind Reading -- EM Weapons -- Neurotechnologies -- Selecting Literature -- Chapter 2: Historical Overview -- The United States -- Russia -- Chapter 3: Brain Control -- Functional Magnetic Resonance Imaging -- Magnetoencephalography -- Transcranial Magnetic Stimulation -- Standard Magnetic Stimulation -- Microwave Auditory Effect -- Brain Wave Monitoring -- Brain-Machine Interface -- Chapter 4: Experimental Grounds for EM Mind Control -- ELF MFs -- Geomagnetic Fluctuations -- Microwave EMFs -- Neurological Effects of EMFs -- Chapter 5: Can Superweak EM Fields Affect Organisms? -- Submicron Level of Magnetoreception -- Magnetic Field Interaction with Molecular Target -- Non-equilibrium States and Biological Sensitivity to EMFs -- Chapter 6: Discussion -- EM Targeting -- Con Arguments -- Social Insignificance -- Failure to Prove -- Technical Lack -- Remote EM Mind Reading Is Not Possible -- Pro Arguments -- Chapter 7: Beyond Science -- Limitations of the Scientific Method -- Reproducibility -- Chapter 8: Conclusion -- References -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electromagnetism -- Physiological effect; Brainwashing; Electronic books